2017
DOI: 10.4155/fmc-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

Advances Toward Lsd1 Inhibitors for Cancer Therapy

Abstract: LSD1 has become an important biologically validated epigenetic target for cancer therapy since its identification in 2004. LSD1 mediates many cellular signaling pathways and is involved in the initiation and development of cancers. Aberrant overexpression of LSD1 has been observed in different types of cancers, and inactivation by small molecules suppresses cancer cell differentiation, proliferation, invasion and migration. To date, a large number of LSD1 inhibitors have been reported, RG6016, GSK-2879552, INC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 64 publications
1
75
0
Order By: Relevance
“…LSD1 is overexpressed in many human cancers which is associated with poor patient survival (8). Increased preclinical data validated LSD1 as an attractive cancer target, resulting in extensive drug discovery efforts (9). So far, most of LSD1 studies focused on its demethylase activity and associated biological functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LSD1 is overexpressed in many human cancers which is associated with poor patient survival (8). Increased preclinical data validated LSD1 as an attractive cancer target, resulting in extensive drug discovery efforts (9). So far, most of LSD1 studies focused on its demethylase activity and associated biological functions.…”
mentioning
confidence: 99%
“…So far, most of LSD1 studies focused on its demethylase activity and associated biological functions. Likewise, all drug discovery efforts on LSD1 targeting were directed to find the demethylase inhibitors (9). However, whether LSD1 has other activities/functions independent of its demethylase activity, and what is the underlying mechanism remain largely unknown, although a recent study showed that ZNF217 naturally interacts with LSD1 to coordinately regulate gene expression independently of its demethylase functions in a prostate cancer model (10).…”
mentioning
confidence: 99%
“…The histone demethylase LSD1 removes mono- and di-methyl marks from H3K4 and H3K9 and shares structural homology with monoamine oxidases (MAOs) in the brain. It can be targeted by several drug candidates 11 and has been therapeutically exploited in other cancers such as acute myeloid leukemia 12 , sarcoma 13 , and neuroblastoma 14 . LSD1 inhibition has been shown to have an enticing therapeutic window that is selective for cancer cells, in part through its disruption of oncogenic and onco-maintenance transcriptional programs 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of LSD1 inhibitors has been developed . LSD1 inhibitors are mainly categorized into two types, irreversible inhibitors and reversible inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of LSD1 selective‐inhibitors is highly desired. Currently, several irreversible LSD1 inhibitors [e. g., ORY‐1001 ( 4 ), GSK2879552 ( 5 ), ORY‐2001, INCB‐059872, IMG‐7289 and CC‐90011] are being tested in clinical trials for cancers and neurodegenerative disorders ,…”
Section: Introductionmentioning
confidence: 99%